2008
DOI: 10.1063/1.2974622
|View full text |Cite
|
Sign up to set email alerts
|

Inexpensive acoustoelectric hydrophone for mapping high intensity ultrasonic fields

Abstract: We describe an inexpensive alternative to conventional hydrophones for measuring ultrasonic fields. The hydrophone, composed of common laboratory supplies, depends on the acoustoelectric (AE) effect, a well-known interaction between electrical current and pressure. Beam patterns of a 540 kHz annular transducer captured using a bowtie graphite hydrophone were consistent with patterns obtained using conventional, more expensive hydrophones. The AE signal was proportional to both the applied bias current (1.83 µV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 9 publications
0
16
0
Order By: Relevance
“…2(c)), consistent with theory and previous studies. [4][5][6][7][8][9][10] Also, a gradual decrease in the AE signal was observed on distant recording electrodes ( Fig. 2(d)) relative to the ground reference.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2(c)), consistent with theory and previous studies. [4][5][6][7][8][9][10] Also, a gradual decrease in the AE signal was observed on distant recording electrodes ( Fig. 2(d)) relative to the ground reference.…”
mentioning
confidence: 99%
“…3 Ultrasound current source density imaging (UCSDI) has been proposed as a complement and possible alternative to traditional mapping of electrophysiological signals. [4][5][6][7][8][9][10][11] UCSDI exploits the acoustoelectric effect (AE), an interaction between pressure and current, to map electric field distributions while scanning a focused ultrasound beam. A previous study in the rabbit heart demonstrated that UCSDI has sufficient sensitivity to map the cardiac activation wave.…”
mentioning
confidence: 99%
“…In figure 3(b), the current density is highest at the center and electrode areas, and decreases quickly away these areas. To avoid the interference of noise, the AE signal at (x 0 , y 0 , z 0 ) is applied band-pass filter with the same center frequency of transducer ( [2], [5]). In figure 4, if the center of beam pattern points at C(x 0 , y 0 , z 0 ), then any point P in the ultrasound pressure field (x, y, z) can be described in the electric field as (x+x 0 , y+y 0 , z+z 0 ).…”
Section: Simulationmentioning
confidence: 99%
“…As an alternative to conventional hydrophones, a new design based on the AE effect has attractive attributes not typically observed in other hydrophones: simple construction, low cost, decent sensitivity, resilience to damage at high intensity ultrasound field, and potentially wider bandwidth and improved sensitivity. The acousto-electric hydrophone [5] can use practically any conductive material. As a result, they are not limited to piezomaterials, possibly leading to novel designs at low cost.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously described a type of inexpensive hydrophone that exploits the AE effect [17]. The AE hydrophone has attractive attributes not typically observed in other hydrophones: simple construction, low cost, high sensitivity, resistance to damage from high-intensity ultrasound fields, and potentially wide bandwidth with an improved design.…”
Section: Introductionmentioning
confidence: 99%